Pengembangan Agenda & Scheduling Meeting Administration and Reporting Application (ASMARA) Di Kantor BPS Lampung Utara - Faris Faris; Maryana Maryana; Dina Anwar; Imam Abrori Hanifan; Khusnul Khotimah (Sienna, 2025)
The inefficiency of manual meeting scheduling at the North Lampung Regency Central Statistics Agency (BPS) has led to frequent data conflicts and communication delays. Conventional calendar applications often fail to accommodate the specific bureaucratic requirement for hierarchical approval before an agenda is publicized. This study aims to develop the Agenda & Scheduling Meeting Administration and Reporting Application (ASMARA) to streamline the scheduling process. The research employs a qualitative applied approach using the Waterfall development method, encompassing requirements analysis, system design, implementation, and testing. The system is built using the Laravel framework and Vue.js, integrated with a Node.js-based WhatsApp Gateway service. The result is a web-based application featuring a role-based approval workflow, where meeting agendas created by staff must be validated by the Head of Office or Sub-division Head. Once approved, the system automatically triggers real-time WhatsApp notifications to all participants. Testing results indicate that ASMARA effectively eliminates scheduling conflicts, ensures administrative accountability through digital approval tracking, and significantly improves information dissemination speed among BPS employees